Differential effect of lithium on cell number in the hippocampus and prefrontal cortex in adult mice: a stereological study. (4th February 2016) - Rajkowska, Grazyna; Clarke, Gerard; Mahajan, Gouri; Licht, Camilla MM; van de Werd, Henri JJM; Yuan, Peter; Stockmeier, Craig A; Manji, Husseini K; Uylings, Harry BM
Abstract : Objectives: Neuroimaging studies have revealed lithium‐related increases in the volume of gray matter in the prefrontal cortex (PFC) and hippocampus. Postmortem human studies have reported alterations in neuronal and glial cell density and size in the PFC of lithium‐treated subjects. Rodents treated with lithium exhibit cell proliferation in the dentate gyrus (DG) of the hippocampus. However, it is not known whether hippocampal and PFC volume are also increased in these animals or whether cell number in the PFC is altered. Methods: Using stereological methods, this study estimated the total numbers of neurons and glia, and the packing density of astrocytes in the DG and PFC of normal adult mice treated with lithium, and evaluated the total volume of these regions and the entire neocortex. Results: Lithium treatment increased the total numbers of neurons and glia in the DG (by 25% and 21%, respectively) and the density of astrocytes but did not alter total numbers in the PFC. However, the volumes of the hippocampus and its subfields, the PFC and its subareas, and the entire neocortex were not altered by lithium. Conclusions: Both neuronal and glial cells accounted for lithium‐induced cell proliferation in the DG. That the numbers of neurons and glia were unchanged in the PFC is consistent with the view that this region is not a neurogenic zone. Further studies are required to clarify the impact of lithium treatment on the PFC under pathological conditions and to investigate the dissociation between increased cell proliferation and unchanged volume in the hippocampus.